Psychometric Properties of the Hungarian UCLA Loneliness Scale Among Adolescents: A Search for the Meaning of Loneliness in the Young Population - Takács, Johanna; Katona, Zsolt Bálint; Ihász, Ferenc (European Journal of Mental Health, 2024)
Introduction: Loneliness has been considered a major public health and policy concern, with substantial physical and mental health impacts. The University of California and Los Angeles Loneliness Scale (UCLA-LS) is one of the most widely used scales for measuring loneliness but it does not have robust psychometric properties among adolescents.Aims: To evaluate the psychometric properties of the Hungarian UCLA-LS among adolescents.Methods: The sample includes a total of 2508 students, 57.3% females, aged between 14 and 21 years. Studying psychometric properties, internal reliability and criterion-related validity were measured. The sample was randomly divided into two parts to examine the factorial structure: one part was used for exploratory factor analysis (EFA) and the other was used for confirmatory factor analysis (CFA).Results: The UCLA-LS showed good internal consistency. Its total score and the single-item measure showed a small correlation, and also indicated a significant moderate association with hopelessness and self-reported well-being. Based on the EFA, we identified two factors with 51.7% of the total variance explained. In the CFA, the two-factor model demonstrated a good fit.Conclusions: The findings suggested that the Hungarian UCLA-LS can be a reliable and valid tool for adolescents to measure some dimensions of loneliness. We confirmed the non-normal, relatively skewed distribution of the scale. We can conclude that the UCLA-LS measures a trait characteristic of loneliness. In the adolescent population, it is recommended to use further measures of loneliness to gain more information about the frequency and nature of the multi-faceted mental representation of loneliness.